Effectiveness and safety of dietary supplements in the adjunctive treatment of psoriasis: a systematic review and network meta-analysis - Chen, Danping; Yang, Jie; Yang, Wenwen; Liu, Xinying; Li, Zhihong (Frontiers in Nutrition, 2025)
BackgroundPsoriasis, a chronic immune-mediated inflammatory skin disease, significantly impairs quality of life. Conventional treatments often pose safety risks or lack long-term efficacy. Dietary supplements show immunomodulatory and anti-inflammatory effects, but their adjunctive role in plaque psoriasis lacks a comprehensive comparison.MethodsA network meta-analysis (NMA) of 21 randomized controlled trials (RCTs), involving 1,463 patients with plaque psoriasis, was conducted using eight international and Chinese databases up to March 3, 2025. Interventions included vitamin D, XP-828L, fish oil, selenium, probiotics, curcumin, and micronutrients. Primary outcomes were Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI), physician global assessment (PGA), interleukins (IL-6, IL-17, IL-23, IL-22), and adverse events. A frequentist NMA in Stata 17.0 used surface under the cumulative ranking curve (SUCRA) to rank efficacy and safety.ResultsIn 21 RCTs (n = 1,463), vitamin D supplementation significantly reduced PASI scores (mean difference = −3.29, 95% confidence interval [CI] − 6.38 to −0.20). XP-828L showed the highest probability of improving DLQI/PGA, and vitamin D + NB-UVB most consistently lowered IL-6/IL-17/IL-23; curcumin reduced IL-22. Adverse events were comparable across interventions (risk ratio 1.02, 95% CI 0.94–1.10). No supplement dominated across all outcomes, and overall certainty was low-to-moderate due to heterogeneity and imprecision.ConclusionDietary supplements may provide complementary benefits in plaque psoriasis; however, effect estimates vary by outcome, and certainty is low to moderate. Personalization is advisable, and confirmatory, larger RCTs with standardized dosing and longer follow-up are warranted. (Word count: 223).Systematic review registrationThe review was registered at INPLASY (INPLASY202570119; DOI:10.37766/inplasy2025.7.0119).